A Critique on the Book Johnson and Sa’di: Two Intimate Strangers - Mostafa Hosseini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Johnson and Sa’di: Two Intimate Strangers, written by Helen Ouliaeinia, is a very useful work in the realm of Persian-English comparative literature. It deals with the unorthodox structural and thematic similarities (and somehow differences) between Johnson’s The History of Rasselas, Prince of Abissinia and S’adi's Golestan. She tries to show documentarily that Johnson’s Rasselas has been probably influenced both structurally and thematically by the great Persian poet and writer Sa’di of Shiraz. The present book falls within the realm of the French school of comparative literature, especially “influence studies”. The present paper is composed of three major sections. The first section introduces the author and his seminal book. The second part tries to discuss the book in terms of formal features. Here, typographical errors and some stylistic shortcomings are highlighted. The last section deals with the content of the book. At the end of this part, some points are suggested to enrich the text. To sum up, it is too difficult to accept the author’s claims about Johnsons’ influences.